2009
DOI: 10.47102/annals-acadmedsg.v38n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Anthropometric Indices for Obesity Screening Among Asian Adolescents

Abstract: Introduction: Weight-and-height-based anthropometric indices have long been used for obesity screening among adolescents.However, the ability of their age-and-sex-specific reference values in classifying adolescent as “obese” in different populations was not fully established. Our study aimed to validate the existing international (BMI-for-age charts from WHO, CDC, IOTF) and local cut-offs [percent weight for height (PWH)] for obesity against body fat percentage, as assessed by 4 skinfolds measurement. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Consequently, comparisons between countries are difficult, as 2 articles in this issue emphasise. 7,8 Both body composition and BMI change with age during childhood and adolescence, and therefore the BMI cut-offs used for defining overweight and obesity in adults cannot be applied directly to children and adolescents.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, comparisons between countries are difficult, as 2 articles in this issue emphasise. 7,8 Both body composition and BMI change with age during childhood and adolescence, and therefore the BMI cut-offs used for defining overweight and obesity in adults cannot be applied directly to children and adolescents.…”
mentioning
confidence: 99%
“…Whereas other surrogate measures of childhood adiposity are used, such as skinfold thickness, the percentage of ideal weight for height, or BMI standard deviation scores specific to the population, the cut-offs set for these measures are arbitrary; they are not based on biological data related to the risk of morbidity later in life. Deurenberg-Yap et al 7 compared the various surrogate measures recommended by international bodies, using a large set of data obtained from a local study of nearly 7000 adolescents. The authors concluded that while the different weight-and-height-based classification systems in Asian adolescents are of comparable validity, with high specificity values, their overall diagnostic accuracy is poorer than expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation